Mitigating market power under tradeable permits - Peter Heindl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
As shown by R. Hahn [6], free allocation equal to the amount of permits a firm with market power uses in equilibrium, can prevent welfare losses. If the necessary amount of free allocation is not provided to the firm with market power, a second best solution is obtained where marginal abatement costs of regulated firms are not equated. In this paper, it is proposed that the government may change the economy wide emissions constraint (cap) as a response to market power, e.g. when free allocation cannot be adjusted. Changing the cap can lead to a situation where marginal abatement costs are equated in the presence of market power. Because changing the cap will lead to changes of social welfare, both effects must be balanced. It is shown that there exists a second best social optimum by balancing the positive effect of limiting market power and the negative effect of changing the cap.
urn:nbn:de:bsz:180-madoc-325894
Keywords: Q53; L12; D21; 330; Tradeable Permits; Market Power; Environmental Regulation